FORMATION OF STUDENTS’ SELF-ASSESSMENT SKILLS IN THE EDUCATIONAL PROCESS - Dadaboyeva Nazira Axmadjonovna (Web of Journals Publishing, 2025)
This article is devoted to the issue of forming students’ self-assessment skills in the educational process. The article considers the essence, importance of self-assessment, the stages, methods and pedagogical conditions for forming students’ self-assessment skills. It also substantiates that through the formation of self-assessment skills, students’ learning activity, independence, responsibility and self-confidence increase.
Keywords: Educational process, self-assessment, self-assessment skills, assessment criteria, reflex.